2019
DOI: 10.1007/s11111-019-00325-6
|View full text |Cite
|
Sign up to set email alerts
|

Where there is smoke: solid fuel externalities, gender, and adult respiratory health in India

Abstract: Chronic respiratory conditions are a leading cause of death in the world. Using data on lung obstruction from the WHO Survey of Global AGEing and Adult Health (WHO-SAGE 2007-08), this paper studies the determinants of respiratory health in India, home to a third of all deaths from Chronic Obstructive Pulmonary Disease. First, we find that smokers and members of households that use solid fuels (wood, biomass, coal or dung) for cooking have higher lung obstruction. Second, even if a respondent's household uses c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 57 publications
(55 reference statements)
0
12
1
Order By: Relevance
“…Existing literature ( Bassani et al, 2010 , Spears, 2012 , Geruso and Spears, 2018 ) has shown that inadequate access to infrastructure, such as piped water, toilets, and clean fuel, can imperil health outcomes for children, which, in turn, can adversely affect children’s learning outcomes. Literature has also demonstrated that the use of solid fuels is closely related to higher levels of household air pollution and disease burden ( Balakrishnan et al, 2011 , Chafe et al, 2014 , Gupta, 2019 ), which can act as serious impediments in children’s human capital development. This paper contributes to a somewhat different dimension of this nexus, that is, the relationship between access to infrastructure and children’s educational outcomes, mediated by a greater time burden on the mother ( Crow & McPike, 2009 ).…”
Section: Resource Dependence and Time Usementioning
confidence: 99%
“…Existing literature ( Bassani et al, 2010 , Spears, 2012 , Geruso and Spears, 2018 ) has shown that inadequate access to infrastructure, such as piped water, toilets, and clean fuel, can imperil health outcomes for children, which, in turn, can adversely affect children’s learning outcomes. Literature has also demonstrated that the use of solid fuels is closely related to higher levels of household air pollution and disease burden ( Balakrishnan et al, 2011 , Chafe et al, 2014 , Gupta, 2019 ), which can act as serious impediments in children’s human capital development. This paper contributes to a somewhat different dimension of this nexus, that is, the relationship between access to infrastructure and children’s educational outcomes, mediated by a greater time burden on the mother ( Crow & McPike, 2009 ).…”
Section: Resource Dependence and Time Usementioning
confidence: 99%
“…are census enumeration blocks. 13 Therefore, PSU identifiers allow us to construct neighborhood-level variables that reflect the characteristics of small localities. For each PSU j in the NFHS, we calculate the fraction of sample respondents that are Muslim, ‾ M j , referred to below as Muslim concentration or Muslim share.…”
Section: A Datamentioning
confidence: 99%
“…Therefore, in panel A of Figure 1, we follow the literature (see, for example, Filmer and Pritchett 2001) in using asset ownership as a proxy for wealth, and collapsing seven categories of asset ownership into a single-dimensional wealth rank within the sample. 14 This gives the horizontal axis 13 Our data do not contain the sampling frame itself. According to the NFHS-3 report, rural PSUs are villages of "usually about 100 to 200 households."…”
Section: B the Puzzlementioning
confidence: 99%
“…The strict lockdown has exposed people to household air pollution like never before. This is a serious concern for a country like India, where more than half of the population is still exposed to household air pollution due to solid fuel use (Balakrishnan et al, 2019 ; Gupta, 2019 ). In India, around 6.7 lakhs deaths a year are attributable to outdoor air pollution and approximately 4.8 lakhs premature deaths a year are linked to household air pollution due to the use of solid fuel (Balakrishnan et al, 2019 ).…”
Section: Overviewmentioning
confidence: 99%